2011
DOI: 10.1155/2011/352580
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting EWS-FLI1 Activity in Ewing's Sarcoma

Abstract: Ewing's sarcoma family tumors (ESFT) are characterized by specific chromosomal translocations, which give rise to EWS-ETS chimeric proteins. These aberrant transcription factors are the main pathogenic drivers of ESFT. Elucidation of the factors influencing EWS-ETS expression and/or activity will guide the development of novel therapeutic agents against this fatal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 134 publications
0
26
0
Order By: Relevance
“…EWS-FLI1 does not transform human cells in vitro , suggesting that the cooperating mutations or related parallel pathways are essential for pathogenesis [18]. Related pathways include p53, INK4A, IGF-1/IGF-1R, bFGF, CD99, and a list of other tyrosine kinase and Wnt pathways [1, 37]. MicroRNAs (miRNAs) are well described in adult cancers and either block target miRNA expression or cause degradation.…”
Section: Fusion Proteins and Targetsmentioning
confidence: 99%
See 3 more Smart Citations
“…EWS-FLI1 does not transform human cells in vitro , suggesting that the cooperating mutations or related parallel pathways are essential for pathogenesis [18]. Related pathways include p53, INK4A, IGF-1/IGF-1R, bFGF, CD99, and a list of other tyrosine kinase and Wnt pathways [1, 37]. MicroRNAs (miRNAs) are well described in adult cancers and either block target miRNA expression or cause degradation.…”
Section: Fusion Proteins and Targetsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are well described in adult cancers and either block target miRNA expression or cause degradation. miRNA-145 has been described as the most active in ESFTs, but other works have shown that other miRNAs could have comparable modulatory effects [37]. Further study of the above pathways, along with RNA processing factors, may shed light onto the specific molecular therapies that could be effective in treating ES/ESFTs.…”
Section: Fusion Proteins and Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional consequences of heterodimerization between EWS/FLI1 and EWS on RNA splicing also have to be revealed [19,50].…”
Section: The Common Role Of Ews and Ews/fli In Transcription And Splimentioning
confidence: 99%